Correlation Between Seismicity Rates and Earthquake Return Periods in the Southern Offshore of West Java, Indonesia - Lulut Alfaris; Andri Wahyudi; Martin Anjar Ginanjar; Ukta Indra Nyuswantoro; Nazish Laeiq (Geosfera: Jurnal Penelitian Geografi, 2025)
The Indian Ocean region south of Java constitutes a highly active seismic zone dominated by the subduction of the Indo-Australian plate beneath the Eurasian plate. This study investigates the seismicity parameters (a-value and b-value) using the Gutenberg-Richter law and estimates the return periods of significant earthquakes. Analyzing earthquake catalog data covering a span of 53 years, we identified the Magnitude of Completeness (Mc) and calculated frequency-magnitude distributions. The results reveal a b-value of 1.17, indicating a region characterized by high material heterogeneity and complex stress release mechanisms. Furthermore, the probabilistic return period for a magnitude 6.5 earthquake is estimated to be approximately 19.24 years. These findings suggest that while the region exhibits frequent moderate-magnitude energy release, the potential for destructive tsunamigenic events remains significant, necessitating robust hazard mitigation strategies for the southern coast of Java.